IMPLIKASI REGULASI PASAR MODAL TERHADAP MOTIF MANAJEMEN LABA: PENGUJIAN BERBASIS TEORI PENSINYALAN - Butar, Sansaloni Butar (Jurnal Akuntansi dan Keuangan Indonesia, 2014)
This study examines the motives for earnings management following a series of regulation released by the Capital Market Supervisory Agency and Indonesian Stock Exchange in 2004. After the release of SK Bapepam-LK and BEJ, this study predicts that the negative effect of board of commissioners on abnormal accruals is more pronounced and the predictive content of abnormal accruals is stronger than previous periods. Results of the study are summarized as follows. First, the negative effect of the board of commissioners on earnings management is stronger after the isssuance of SK Bapepam-LK and BEJ. Second, the predictive content of abnormal accruals is stronger for periods 2004-2010 than that for 2001-2003. Third, the addition of independent members to become majority in the board of commissioner does not alter the predictive content of accruals. Overall, the results indicate that SK Bapepam-LK and BEJ have successfully increased the monitoring function of board of commissioners. This paper contributes to the current debates in earnings management studies regarding the motivation for earnings management (signaling versus private gain). In addition, the evidence indicates the inconsistent results of previous earnings management studies in Indonesia with respect to the role of independent commissioners stem from the passage of regulation on corporate governance that took place in 2004.